Optimal outcome sharing with a consortium of contractors - Hosseinian, S. Mahdi; Carmichael, David G. (Journal of Civil Engineering and Management, 2016)
Where a consortium of contractors is involved, there exist no guidelines in the literature on what the outcome sharing arrangement should be. The paper addresses this shortfall. It derives the optimal outcome sharing arrangement for risk-neutral and risk-averse contractors within the consortium, and between the consortium and a risk-neutral owner. Practitioners were engaged in a designed exercise in order to validate the paper’s propositions. The paper demonstrates that, at the optimum: the proportion of outcome sharing among contractors with the same risk-attitude should reflect the levels of their contributions; the proportion of outcome sharing among contractors with the same level of contribution should be lower for contractors with higher levels of risk aversion; a consortium of risk-neutral contractors should receive or bear any favourable or adverse project outcome respectively; and the proportion of outcome sharing to a consortium of risk-averse contractors should reduce, and the fixed component of the consortium fee should increase, when the contractors become more risk-averse or the level of the project outcome uncertainty increases. The paper proposes an original solution to the optimal sharing problem in contracts with a consortium of contractors, thereby contributing to current practices in contracts management.First published online: 14 Sep 2015